Occurrence of the Omicron variant of SARS-CoV-2 in northern Viet Nam in early 2022 - Ung, Trang thi Hong; Hoang, Phuong Vu Mai; Nguyen, Son Vu; Nguyen, Hang Le Khanh; Nguyen, Phuong thi Kim; Phan, Dan Tan; Le, Thanh Thi; Nguyen, Anh Phuong; Nguyen, Thach Co; Hasebe, Futoshi; Le, Mai thi Quynh (Western Pacific Surveillance and Response, 2022)
The Omicron variant caused a surge of infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Viet Nam in early 2022, signalling community transmission. We report on active whole-genome sequencing surveillance of positive SARS-CoV-2 samples collected at that time in northern Viet Nam from international arrivals and community clusters. We used an amplicon protocol developed with 14 polymerase chain reaction products and the Illumina iSeq 100 platform. Overall, 213 nasopharyngeal or throat swabs were analysed, of which 172 samples were identified with the Omicron variant. Of these, 80 samples were collected from community cases in February 2022, among which 59 samples were sublineage BA.2 and one sample was the recombinant XE variant. Our results indicated that Omicron had replaced Delta as the dominant variant in a very short period of time and that continuously conducting active whole-genome sequencing surveillance is necessary in monitoring the evolution and genomic diversity of SARS-CoV-2 in Viet Nam.
Keywords: SARS-CoV-2 omicron subvariant BA.2; COVID-19; whole genome sequencing; Viet Nam; imported infection; community transmission